The clinic and elsewhere : addiction, adolescents, and the afterlife of therapy - Meyers, Todd (In vivo (Seattle, Wash.), 2013)
Despite increasingly nuanced understandings of the neurobiology of addiction, and a greater appreciation of the social and economic conditions that allow drug dependency to persist, there remain many unknowns regarding the individual experience of substance abuse and its treatment. In the early twenty-first century, novel pharmaceutical therapies have given rise to both new hopes for recovery and renewed fears about drug diversion and abuse. In this book, the author looks at the problems of meaning caused by drug dependency and appraises the changing terms of medical intervention. By following a group of adolescents from the time they enter drug rehabilitation treatment through their reentry into the outside world - the clinic, their homes and neighborhoods, and other institutional settings - the author traces patterns of life that become mediated by pharmaceutical intervention. His focus is not on the drug economy but rather on the therapeutic economy, where new markets, transactions of care, and highly porous conceptions of success and failure come together to shape addiction and recovery. The book is at once a meditative work of anthropology, a demonstration of the theoretical and methodological limits of medical research, and a forceful intervention into the philosophy of therapeutics at the level of the individual. -- Book jacket.